-8d-5d+7d=7d

Simple and best practice solution for -8d-5d+7d=7d equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8d-5d+7d=7d equation:


Simplifying
-8d + -5d + 7d = 7d

Combine like terms: -8d + -5d = -13d
-13d + 7d = 7d

Combine like terms: -13d + 7d = -6d
-6d = 7d

Solving
-6d = 7d

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-7d' to each side of the equation.
-6d + -7d = 7d + -7d

Combine like terms: -6d + -7d = -13d
-13d = 7d + -7d

Combine like terms: 7d + -7d = 0
-13d = 0

Divide each side by '-13'.
d = 0

Simplifying
d = 0

See similar equations:

| x^4+6x^2=1 | | x/3=4x-55 | | -33x=-165 | | 4b+22=50 | | x/26=12/13 | | 8|1/8|=0 | | -5x+7-3x=-4x-5-2x | | 10y+19x= | | -4*(20-(1/3*x)) | | 0=0.2(5x+6)+1.2 | | 10y+19x+16x+4z= | | -4*(20-(1/3*x | | (X/3)-(x/4)=20 | | h(x)=2x-6 | | 2(x-2)3=3(2x+6) | | X/3-x/4=20 | | 9/8*c-2c=13 | | -(-x+4)+2x-3+x^2=x^2-4x+14 | | 147=4.9x-38 | | y=x+420 | | 6*(x-5)=6*x-6*5 | | (10y-8)-(40x+20y-7)= | | t(4t-9)=0 | | 96=8.5x | | .85x=96 | | 85/100=96/x | | 7/4-3/5 | | 3x+39=3x-71 | | Y=a/1-h | | 2x-4)*(5/7) | | 3x+4x=100+4x | | -4/3=2/32 |

Equations solver categories